STUDENTS CONCEPTIONS OF THE ENERGY CRISIS: A CROSS-SECTIONAL STUDY - Melati, Putri Sekar; Rustama, Nuryani; Rusyati, Lilit (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
This cross-sectional study looks at how junior high and elementary school students think about crisis energy. The tool is sent out through an open-ended online survey. There were 167 people who took part in the study. The number of sixth-grade elementary school students (14), seventh-grade students (51), eighth-grade students (6), and ninth-grade students (96) in Bandung City. The study's results showed that ninth-grade students came up with the most ideas, followed by eighth- and seventh-grade students. The ninth graders came up with the idea that